Respuesta :

Answer:

see explanation

Step-by-step explanation:

Using the rules of logarithms

• log x + log y = log xy

• log x - log y = log ([tex]\frac{x}{y}[/tex] )

• log[tex]x^{n}[/tex] = n log x

(a)

[tex]log_{7}[/tex] 9 + [tex]log_{7}[/tex] 2 = [tex]log_{7}[/tex] (9 × 2) = [tex]log_{7}[/tex] 18

(b)

[tex]log_{8}[/tex] 7 - [tex]log_{8}[/tex] 11 = [tex]log_{8}[/tex] [tex]\frac{7}{11}[/tex]

               ↑ required value

(c)

2[tex]log_{9}[/tex] 2 = [tex]log_{9}[/tex] 2² = [tex]log_{9}[/tex] 4